Impact of spiritual care program on self-efficacy and burden in mothers of children with leukemia - Shahpar Bagheri; Zahra Sharifi Rigi; Maryam Paran; Parvin Ghaemmaghami; Zahra Hadian Shirazi; Rozhan Ghobadimoghaddam (BMC Psychology)
Abstract Background Taking care of children with Leukemia leads to a burden and decreases their caregivers’ self-efficacy. This study aimed to evaluate whether training spiritual care program impacts the self-efficacy and burden of mothers having children with Leukemia. Methods This randomized clinical trial was conducted on sixty-four mothers caring for their children with Leukemia, who were randomly allocated into eighteen blocks of 4 using computerized random allocation, 32 individuals were assigned to the intervention group and 32 to the control group. A training spiritual care program based on the Sound heart model was performed individually through four 30-45-minute face-to-face sessions during four weeks and a four-week follow-up. The setting was the chemotherapy department in Imam Reza educational, specialty and subspecialty clinic, affiliated with the Shiraz University of Medical Science. The data were collected using a demographic information form, the Caregiver self-efficacy questionnaire and the Caregivers Burden Inventory. The data were analyzed via descriptive and inferential statistics. All tests were two-tailed, and the statistical level was considered 0.05. Results Before intervention, there was no significant difference between the control and intervention groups in terms of self-efficacy and the caregiver burden mean score (p > 0.05). However, after the intervention a significant difference was observed between the two groups in self-efficacy scores [95% CI: -80.37, -57.74] and Caregiver Burden scores [95% CI: 10.34, 20.28] (p < 0.001). Also, the mean scores of caregivers’ burden was decreased, and self-efficacy increased significantly from pre-intervention to post-intervention in the intervention groups (p < 0.001). At the same time, there were no significant differences in the control groups. Also, there was a significant and reverse correlation between self-efficacy and caregiver burden (r = 0.678, P < 0.001). Conclusion Spiritual care program based on the Sound heart model improves self-efficacy and decreases caregivers’ burden in mothers of children with Leukemia. The use of this model is recommended for addressing the spiritual needs of mothers with children diagnosed with leukemia and for guiding health professionals in developing spiritual and healing care programs in clinical practice. Trial registration IRCT20210410050924N1 Registration date 20,210,504.